PENGARUH HIMBAUAN, KONSELING DAN PEMERIKSAAN TERHADAP POTENSI PENERIMAAN PAJAK SEKTOR USAHA REAL ESTAT DALAM ERA SELF ASSESSMENT SYSTEM (STUDI PADA KANTOR PELAYANAN PAJAK PERUSAHAAN MASUK BURSA) - Apriana, Dwi Sara (Jurnal Mahasiswa Perpajakan, 2014)
This research aims to analyze and explain the influence effect of appeal, counseling and audit done by fiscus to the potential tax revenues in the real estate sector. This research used explanatory research with quantitative approach. The sample of this research is taken by using purposive sampling technique. The researcher used questionnaire to fiscus especially Account Representative who are handling 36 real estate companies listed in the Indonesia stock exchange. Using descriptive and multiple linear regression, this study showed that appeals and counselingÂ  do not influence the pential tax revenues. Meanwhile, the potential tax revenues are influenced by audit significantly. Together, however, appeals, counseling, and audit significantly influence the tax revenues. Keywords: Appeal, Counseling, Audit, Tax Revenue